Modelagem para a mensuração de desempenho dos sistemas Bus Rapid Transit no Brasil - Neuenfeldt Júnior, Alvaro Luiz (2014)
It is notorious the role of urban displacements within the evolutionary social context, economic and cultural societies over the past centuries, being one of the most important activities and concern regarding the administration and planning of cities, so that more than half of the world's population is directly involved in any of these locations. In view of this scenario, various activities have been planned recently in order to improve the urban mobility conditions, in particular for the system called Bus Rapid Transit (BRT), which demands of its responsible proactively management tools about the situation of the local operation. Therefore, this paper aims to propose a modeling for performance measurement on transport BRT in Brazil that helps their managers for the efficient management of the system. Methodologically, the concepts described by multi-criteria Approach, in order to be able to refer the competitiveness level of the factors in the industry. To end, the application includes the verification of the situation of twelve cities with BRT and more than one million inhabitants in Brazil, where it was noted that the city of Curitiba (j9 = 89%) has the system with better conditions of installation in the country, whose level of evaluation is in the default "Satisfactory", followed by Rio de Janeiro (j2 = 81%), Recife (j3 = 78%) and São Paulo (j1 = 78%), in order to comply with acceptable reliability level research in demand.